Experimental Study on the Effect of Micro Concentrations of Hybrid Nanofluids through Microchannel Heat Sinks - Mohamed Elsherbiny; Mostafa Ali; Moatsem Shahin; Mahmoud El-Kady (Journal of Applied and Computational Mechanics)
The current study examines the convective heat transfer coefficient experimentally. It assesses the performance of Al2O3, CuO, ZnO, and Ag/ distilled water nanofluids up to a tetra level of hybridization utilized in microprocessor cooling systems equipped with MCHS. An equal ratio of 50%, 33.3%, and 25% for di-, tri-, and tetra-nanofluids, respectively, with a focus on micro-volume fraction 0.025% and comparing it with 0.05%. Operating conditions were as follows: heat loading from 136.4 up to 196.4 watts; and flow rate from 0.35 up to 0.5 LPM. The findings showed that all types of mono nanofluids showed an increase in Nu and HTC enhancement levels by increasing concentration from 0.025% to 0.05%, while HYNF reacted the opposite, even lower than the base fluid values. The reasons behind such findings might be due to the nanoparticle agglomeration effect. The maximum PEC was 1.845 at the highest heat flux and flow velocity by Al2O3-ZnO-Ag, while the minimum PEC was 0.847 at the highest heat flux and lowest velocity by CuO-ZnO-Ag, which is lower than unity. ZnO, Al2O3-CuO-ZnO, and CuO-ZnO-Ag only showed a PEC lower than unity; however, not in all operating conditions. Despite their differences in magnitude at 0.025%, all nanofluids showed an enhancement in terms of Nu and HTC ratios.